2019
DOI: 10.17770/sie2019vol6.3789
|View full text |Cite
|
Sign up to set email alerts
|

Management of Psychosocial Risks in the Educational Sector of Latvia

Abstract: Risk management is gaining acknowledgement in organisational management due to the benefits it brings with it, such as ability of managers to forecast possible threats and plan the most appropriate prevention measures. Psychosocial risk group is one of the largest risk group types and is related to the aspects of staff overburning, lack of employee motivation, health problems due to stress, etc. Study carried in Latvia about risk management showed that psychosocial risks are significant for educational institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, it can also be seen that 19.17% are also exposed at times. This compares with 40.49% who said they were free from PSRs, which is largely due to the other items in the domain (Jones-Rincon & Howard, 2019;Jemeljanenko & Geske, 2019;Anonyme, 2009). In addition, we found that 57.75% of students were exposed to PSRs as a result of insufficient study time (75%), high pace of tutorials (74%) and maintaining a high pace of study (68%).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…However, it can also be seen that 19.17% are also exposed at times. This compares with 40.49% who said they were free from PSRs, which is largely due to the other items in the domain (Jones-Rincon & Howard, 2019;Jemeljanenko & Geske, 2019;Anonyme, 2009). In addition, we found that 57.75% of students were exposed to PSRs as a result of insufficient study time (75%), high pace of tutorials (74%) and maintaining a high pace of study (68%).…”
Section: Discussionmentioning
confidence: 83%
“…This means an average of 2111 cases of occupational injuries per year versus 9 cases of occupational diseases. In terms of percentage, this represents 99.5% for accidents and 0.5 for occupational disease (Jones-Rincon & Howard, 2019;Jemeljanenko & Geske, 2019). We are far from the ILO data, in which accidents occupy 14% and occupational diseases 86%.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…As the literature is reviewed, it is seen that there are many factors, which affect the psychosocial risks of the teachers [2][3][4]. Souto et al [2] investigated psychosocial factors associated with the development of job-related distress in the specific professional context of higher education teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Authors aimed to determine which dimensions of psychosocial risk were associated with work-related distress. Jemeļjanenko et al [3] proposed a freamwork to investigate various methods researched by other authors on how to manage risk, analyze the causes of these risks, and make recommendations on how to deal with psychosocial risks in the education sector. Heredia et al [4] explored the adaptation and validation of "CoPsoQ-Istas 21" in the Ecuadorian environment.…”
Section: Introductionmentioning
confidence: 99%